Valproic acid induced acute necrotizing pancreatitis - Gurung, Rabindra; Subedi, Asish; Bhattarai, Balkrishna (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Valproic acid induced pancreatitis is a rare entity with an estimated incidence of one in 40000. Occurrence of acute necrotizing pancreatitis is even more uncommon with only very few cases being reported till date. We present a case of valproic acid associated acute necrotizing pancreatitis that complicated to develop pancreatic pseudo cyst. Case discussion: A 21-year-old male presented in our emergency room with sudden onset of severe epigastric pain along with nausea and vomiting. He gave history of having on valproic acid therapy for the last 13 months for seizure disorder. There was no history suggestive of gall stone disease, alcohol intake, hyperlipidemia, abdominal trauma or any surgical intervention. Clinical suspicion of acute pancreatitis was confirmed by revealing of necrotizing pancreatitis in contrast enhanced computerized tomography. Patient was admitted in the intensive care unit where valproic acid was stopped and phenytoin started. Clinical improvement was observed with conservative management while mild intermittent abdominal pain, nausea and vomiting persisted. Repeat computerized tomography done later revealed features of pancreatic pseudo cyst for which patient underwent definitive surgical management. Conclusions: Today, valproic acid is widely used for multiple disease conditions. Starting from 1979 till 2010, 107 cases of valproic acid induced acute pancreatitis have been reported. Acute pancreatitis is a serious condition with significant mortality despite optimal treatment. Unfortunately, it is underreported and underestimated especially following valproic acid use. Increasing frequency of valproic acid associated pancreatitis demands reconsideration of its use. Journal of Society of Anesthesiologists 2014 1(2): 86-88